Facial nerve reconstruction for flaccid facial paralysis: a systematic review and meta-analysis - Zumbusch, Friedemann; Schlattmann, Peter; Guntinas-Lichius, Orlando (Frontiers in Surgery, 2024)
Objectives: To determine the functional outcome after facial nerve reconstruction surgery in patients with flaccid facial paralysis.Methods: Systematic review and meta-analysis on studies reporting outcomes after direct facial nerve suture (DFS), facial nerve interpositional graft suture (FIGS), hypoglossal facial nerve suture (HFS), masseteric-facial nerve suture (MFS), and cross-face nerve suture (CFS) using were identified from PubMed/MEDLINE, Embase, Web of Science databases. Two independent reviewers performed twostage screening and data extraction. A favorable result was defined as a final House-Brackmann grade I-III and is presented as ratio of all patients in percentage. Pooled proportions were calculated using random-effects models.Results: From 4,932 screened records, 54 studies with 1358 patients were included.A favorable result was achieved after DFS in 42.67% of the patients (CI: 26.05% to 61.12%), after FIGS in 66.43% (CI: 55.99% to 75.47%), after HFS in 63.89% (95% CI: 54.83% to 72.05%), after MFS in 63.11% (CI: 38.53% to 82.37%), and after CFS in 46.67% (CI: 24.09% to 70.70%). There was no statistically significant difference between the techniques (Q = 6.56, degrees of freedom = 4, p = 0.1611).The established facial nerve reconstruction techniques including the single nerve cross transfer techniques produce satisfactory results in most of the patients with permanent flaccid facial paralysis. An international consensus on a standardized outcome measures would improve the comparability of facial reanimation techniques.